MORAL VALUES AS PRINCIPLE OF SURVIVING IN THE MOVIE TO KILL A MOCKINGBIRD BY ROBERT MULLIGAN - Saputra, Muhammad Ade; Latumeten, Anna Anganita Theresia (Prologue: Journal on Language and Literature, 2026)
Moral is one of the most important things to be possessed in a person’s life, the absence of moral can lead to decisions that prioritize personal gain over the well-being of others. It can result in systemic injustices, human rights violations, and societal unrest. This study aims to discuss about the forms of moral values that shown in the movie, and how the forms of moral values are used as principle of surviving in the movie To Kill a Mockingbird by Robert Mulligan. The method used in this study is qualitative descriptive, as for the data they are collected from scenes from the movie. Dialogue and actions in the movie as primary data, in addition, the researcher utilizes secondary data such as books, journals, and previous studies to help analyze and solve the research questions of this study. The result of this study is the researcher found forms of moral values contained in the movie and the moral values found indeed can be used as principle of surviving. Atticus moral behavior helps him maintain a good and peaceful life.